The effect of human Mesenchymal stem cell on neutrophil oxidative burst - Ramasamy, Rajesh; Krishna, K.; Maqbool, Maryam; Vellasamy, Shalini; Sarmadi, Vahid Hosseinpour; Abdullah, Maha; Vidyadaran, Sharmili (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2010)
Objective: Mesenchymal stem cells (MSC) are multipotent, non-haematopoietic stem cells that are capable of differentiating into different varieties of mature cell types such as osteoblasts, chondrocytes, adipocytes. and myoblasts. There is abundant evidence showing that MSC not only affect the differentiation of haematopoietic progenitors, but also the function of mature cells like lymphocytes and neutrophils. However the effect of MSC on neutrophil function and its responses is not well studied. Therefore, this study was conducted to assess the effect of MSC on neutrophil nitric oxide production. Method: Neutrophils from heparanised venous blood were isolated using Ficoll-Hypaque density gradient centrifugation followed by Dextran sedimentation and red blood cell (RBC) lysis. Isolated neutrophils were on average of 97% purity as determined by morphologic analysis. MSC were generated from human bone marrow and characterised by immunophenotyping (monoclonal antibodies CD1O5, CD73 and CD34) using a flowcytometer. In order to test the effects of MSC on neutrophil function, isolated neutrophils were co-cultured in the presence or absence of MSC at different ratios for 24 and 48 hours. The amount of nitric oxide released was used as an indication of oxidative burst and measured using the Griess assay. Result: The results indicate that MSC neither elevate the NO level when cocultured with resting neutrophils nor alone. However MSC profoundly inhibit the secretion of nitric oxide in PMA stimulated neutrophils after 241w of incubation. Conclusion: MSC exert an immunomodulatory effect on neutrophil by suppressing neutrophil oxidative burst in vitro.